Cement-within-cement technique in revision reverse total shoulder arthroplasty: complications, reoperations, and revision rates at 5-year mean follow-up - Rodrigo de Marinis, MD; John W. Sperling, Jr.; Erick M. Marigi, MD; Ausberto Velasquez Garcia, MD; Eric R. Wagner, MD; Joaquin Sanchez-Sotelo, MD, PhD (JSES Reviews, Reports, and Techniques)
Background: Revision reverse total shoulder arthroplasty (rTSA) of a previously cemented humeral component is challenging. In hip arthroplasty, the cement-within-cement (CwC) technique has been well described as an effective option. However, for shoulder arthroplasty there remains a paucity of data investigating this technique. The purpose of this study was to determine the mid-term outcomes of patients who underwent a revision rTSA utilizing the CwC for management of the humeral component. Methods: Between 2005 and 2021, 68 revision rTSA using the CwC technique with a minimum of 2 years clinical follow-up were identified from a single institution joint registry database. Revised implants consisted of 38 (55.9%) hemiarthroplasties, 22 (32.4%) anatomic total shoulder arthroplasties, and 8 (11.8%) rTSA. A total of 12 (17.6%) shoulders required an osteotomy (corticotomy or window) to assist with extraction of the cemented stem. The mean follow-up after revision was 5.4 years (range, 2-16 years). Surgical complications, reoperations, revisions, and implant survivorship were assessed. Results: Of the 12 shoulders that required an osteotomy for component removal, 11 (91.7%) were healed. At final follow-up, the overall complication rate was 26.9%. The most common complication was fracture or fragmentation of the greater tuberosity (20.6%, n = 13) with 10 (76.9%) cases showing signs of healing at final follow-up. The overall survivorship free of revision surgery was 88.2% at 2 and 80.9% at 5 years, respectively. The most frequent causes of re-revision surgery were aseptic glenoid component loosening (n = 4) and instability (n = 4), with only 2 (2.9%) patients developing humeral component loosening (at 2 and 5 years, respectively). Male sex was associated with an increased risk of revision surgery (hazard ratio [HR], 3.52 [95% confidence interval [CI] 1.22-10.18]; P = .02) and complications (HR, 3.56 [95% CI, 1.40-9.07]; P = .008). The grade of postoperative lucent lines at the humerus (HR, 1.35 [95% CI, 1.04-1.74]; P = .02) and glenoid (HR, 1.59 [95% CI, 1.22-2.10]; P = .001) also correlated with an increased risk of re-revision surgery. Conclusion: The CwC technique is a reliable option for revising previously cemented humeral components in revision rTSA. Although a low rate of humeral component loosening was observed, higher rates of complications and re-revision surgery were observed over time secondary to aseptic glenoid component loosening and instability, which are not directly related to CwC technique but to revision surgery in general.